Nonperturbative matching between equal-time and lightcone quantization - Fitzpatrick, A. Liam; Katz, Emanuel; Walters, Matthew T. (The journal of high energy physics, 2020)
A bstract We investigate the nonperturbative relation between lightcone (LC) and standard equal-time (ET) quantization in the context of λϕ 4 theory in d = 2. We discuss the perturbative matching between bare parameters and the failure of its naive nonperturbative extension. We argue that they are nevertheless the same theory nonperturbatively, and that furthermore the nonperturbative map between bare parameters can be extracted from ET perturbation theory via Borel resummation of the mass gap. We test this map by using it to compare physical quantities computed using numerical Hamiltonian truncation methods in ET and LC.